Overwork in Spouse's Degree Field and the Labor Market Outcomes of Skilled Women - Terra McKinnish (Institute of Labor Economics (IZA), 2019)
This paper estimates the effect of overwork and underwork in husband's undergraduate degree field on the labor market outcomes of skilled married women using 2009-2015 ACS data. Overwork and underwork by degree field, respectively, are measured as the fraction of prime-aged men reporting 50 or more and 34 or fewer usual hours of work per week. Analysis is conducted using the sample of college-educated men and women ages 25-44 married to college-educated spouses. Results indicate that for married women with children, overwork in spouse's degree field negatively affects total earnings, hourly wages, employment and hours of work relative to married men with children or married women without children. There is little evidence that underwork in spouse's degree field differentially affects married women with children.
Keywords: J16; J22; 330; marriage; labor market; spouse hours of work; degree field